2015
DOI: 10.1089/aid.2014.0278
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Lipids and Cardiovascular Risk After Switching HIV-1 Patients on Nevirapine and Emtricitabine/Tenofovir-DF to Rilpivirine/Emtricitabine/Tenofovir-DF

Abstract: Antiretroviral therapy-related dyslipidemia increases the risk of cardiovascular disease (CVD) and is less frequently observed with nevirapine. Whether substituting rilpivirine for nevirapine has dyslipidemic consequences and alters CVD risk is unknown. The aim of this prospective open-label clinical trial was to evaluate serum lipids, cardiovascular risks, and lipid treatment goals over 48 weeks after switching from nevirapine to rilpivirine. Fifty HIV-1-suppressed patients on stable once-daily nevirapine plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…However, a prospective open-label clinical trial that evaluated the cardiometabolic outcomes after HIV-infected participants were switched from an older generation (nevirapine) to a newer generation NNRTI (rilpivirine) demonstrated a mean systolic blood pressure decrease of 6.0 mm Hg (95% CI −1.7 to −10.3; P=0.007) after 24 weeks of therapy. 103…”
Section: Mechanismsmentioning
confidence: 99%
“…However, a prospective open-label clinical trial that evaluated the cardiometabolic outcomes after HIV-infected participants were switched from an older generation (nevirapine) to a newer generation NNRTI (rilpivirine) demonstrated a mean systolic blood pressure decrease of 6.0 mm Hg (95% CI −1.7 to −10.3; P=0.007) after 24 weeks of therapy. 103…”
Section: Mechanismsmentioning
confidence: 99%
“…In these studies, TDF/FTC/RPV was found to be non-inferior to several different ART regimens, including protease inhibitor (PI)- and NNRTI-based combinations. 22,23,24,25 Hence, in Europe and the United States, TDF/FTC/RPV is indicated for use in treatment-naive patients with HIV-1 RNA ≤ 100 000 copies/mL and for patients with suppressed viral load for ≥ 6 months prior to switching therapy and without known resistance-associated mutations to NNRTIs, TDF or FTC. 26,27…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, an increase in HDL cholesterol under nevirapine use has been previously described [ 32 ]. Whether this also translates into decreased cardiovascular risk for nevirapine users is unclear as large trials are lacking and circumstantial evidence is ambiguous [ 33 , 34 ]. In contrast, INSTI users showed an up to 1.5 fold increase in HDL cholesterol clusters compared to doravirine users, indicating a more favorable CVD lipid risk profile in INSTI users.…”
Section: Discussionmentioning
confidence: 99%